Faith, Favour, and Fervour: Emotions and Conversion among the Early Dominicans. (22nd May 2015) - Young, Spencer E.
Abstract : In the later Middle Ages, the term conversio could be applied to a variety of different processes. One of its predominant senses meant affiliation with a particular religious order. This article explores the roles played by the emotions in thirteenth‐century conversion narratives, and focuses especially on those involving the early Dominican order. It argues that the emotional content in these narratives (ranging from fear to tears) performed crucial tasks, such as the authentication of a convert's sincerity, or the articulation of the order's legitimacy against its contemporary critics. While the emotions do not necessarily offer a more authentic historical account of any particular conversion, they are critical for understanding the many ways in which the experience of conversion accomplished meaningful personal and institutional ends during this period.